Pengembatan Web Try Out untuk Kemampuan Bahasa Inggris untuk Siswa di Indonesia - Riverinda Rijadi, Safara Cathasa; Fadhil, Iqbal (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2025)
English proficiency plays a crucial role in enhancing students' academic performance, cultural awareness, and career opportunities. However, many Indonesian students still face difficulties in mastering English due to traditional teaching methods that offer limited exposure to real-world communication. This study aims to design and develop an English qualification try-out website to support students' learning using the Feature-Driven Development (FDD) method. The system's usability and user experience were evaluated through the System Usability Scale (SUS) and the Short User Experience Questionnaire (UEQ-S). The SUS evaluation produced a score of 72.46, classified as Good and above the industry average, indicating practical usability. The UEQ-S results showed a Pragmatic Quality score of 1.810, a Hedonic Quality score of 0.988, and an overall average of 1.399, indicating a positive user experience. These findings demonstrate that the proposed system effectively supports English learning activities while maintaining a user-friendly interface. Future development should focus on enhancing interactivity and engagement to further improve the overall learning experience.